Support plate and electronic equipment
By using the composite materials of the laminated high-stiff first reinforced fiber layer, the mesophase asphalt-based carbon fiber layer and the second reinforced fiber layer, the problems of insufficient thermal conductivity of the folding screen mobile phone support plate and difficult to take into account both the structural strength and the lightweighting needs, and the thinning, thermal conductivity and high stiffness properties of the composite materials are achieved.
Patent Information
- Application Number
- CN202420833144.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2034-04-19
AI Technical Summary
The existing folding screen mobile phone support plates lack thermal conductivity during the use of 5G electronic devices, which makes it difficult to effectively transfer the heat generated by electronic components, and it is difficult to take into account both structural strength and lightweight requirements.
The composite material of the laminated high-stiff first reinforced fiber layer, the mesophase bitumen-based carbon fiber layer and the second reinforced fiber layer is adopted. The mesophase bitumen-based carbon fiber layer has thermal conductivity and high stiffness, and the overall stiffness of the first reinforced fiber layer and the second reinforced fiber layer reinforced the composite material.
It realizes the lightweight, good thermal conductivity and high stiffness of composite materials, can effectively transfer heat from electronic components, disperse stress during folding, and extend service life.
Smart Images

Figure CN222769117U_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of supporting materials, and in particular to a composite material, a supporting plate and an electronic device. Background Art
[0002] With the continuous development of electronic devices such as mobile phones, users' demand for large-screen mobile phones has increased, but large-screen mobile phones are inconvenient to carry. Therefore, foldable screen mobile phones with extendable and deformable screens have become the main research direction. The foldable screen mobile phone connects the screen components of two adjacent areas through a hinge assembly. Specifically: the hinge assembly includes a hinge structure and a support plate. The screen assembly is covered on the support plate. The support plate and the hinge structure are rotatably connected, so that the adjacent screen assemblies can achieve smooth and safe folding and unfolding of the foldable screen mobile phone through the cooperation of the support plate and the hinge structure. During the folding and unfolding process of the foldable screen mobile phone, the support plate can effectively transfer the heat of the electronic components to the housing or other heat dissipation paths, and disperse the stress generated by the mobile phone during the folding process, reducing the problem of damage to the screen assembly due to uneven force during the folding and unfolding process.
[0003] However, the use of 5G electronic devices currently requires more signal and network data transmission, which causes the heat generated by electronic components, batteries, screen components and other structures in foldable screen mobile phones to increase sharply. At the same time, in order to meet users' higher performance requirements and thinner design requirements for foldable screen mobile phones, the performance requirements of the support plate put forward better design and manufacturing requirements. Therefore, finding a new material to prepare a thinner, stronger and more thermally conductive support plate is an issue that electronic equipment manufacturers need to consider. Utility Model Content
[0004] In view of this, the present application provides a composite material, a support plate and an electronic device, which ensures the thermal conductivity and high stiffness requirements of the composite material while reducing the thickness of the composite material by stacking a high-rigidity first reinforcing fiber layer, an intermediate phase asphalt-based carbon fiber layer and a second reinforcing fiber layer.
[0005] In a first aspect, the present application provides a composite material, comprising at least one first reinforcing fiber layer, at least one second reinforcing fiber layer, and an intermediate phase asphalt-based carbon fiber layer arranged therebetween; wherein the first reinforcing fiber layer is an acrylonitrile-based carbon fiber layer or an asphalt-based carbon fiber layer, and the second reinforcing fiber layer is an acrylonitrile-based carbon fiber layer or an asphalt-based carbon fiber layer.
[0006] In some feasible embodiments, the carbon fibers in the mesophase pitch-based carbon fiber layer are arranged in at least one of a unidirectional structure and a woven fabric structure.
[0007] In the above scheme, the unidirectional structure means that all carbon fibers are arranged in the same direction. This arrangement allows the mesophase asphalt-based carbon fiber layer to have extremely high strength and rigidity in the fiber arrangement direction. The woven fabric structure means that multiple carbon fiber yarns are interwoven in a specific weaving method (such as plain, twill, satin, etc.). This arrangement allows the mesophase asphalt-based carbon fiber layer to have certain strength and rigidity in multiple directions.
[0008] In some feasible implementations, the thickness of the mesophase asphalt-based carbon fiber layer is 20 μm to 200 μm.
[0009] In the above scheme, the intermediate phase asphalt-based carbon fiber layer is arranged between the first reinforcing fiber layer and the second reinforcing fiber layer for the heat conduction process. If the thickness of the intermediate phase asphalt-based carbon fiber layer is too large, the mass increases, which will affect the total mass of the composite material, resulting in the composite material failing to meet the lightweight requirements; if the thickness of the intermediate phase asphalt-based carbon fiber layer is too thin, the stiffness of the intermediate phase asphalt-based carbon fiber layer is reduced, and defects such as deformation or cracks are prone to occur during use, affecting the service life of the intermediate phase asphalt-based carbon fiber layer.
[0010] In some feasible implementations, the thermal conductivity of the mesophase asphalt-based carbon fiber layer is ≥400 W / m·K.
[0011] In the above scheme, the thermal conductivity of the intermediate phase asphalt-based carbon fiber layer is an important parameter to measure the thermal conductivity of the intermediate phase asphalt-based carbon fiber layer. If the thermal conductivity of the intermediate phase asphalt-based carbon fiber layer is too small, the thermal conduction efficiency of the intermediate phase asphalt-based carbon fiber layer is not high, and the heat generated by the internal components of the electronic device cannot be quickly and effectively transferred to the outer casing or other heat conduction paths, which can easily cause the internal components to be in a high temperature state for a long time, affecting the service life of the internal components.
[0012] In some feasible implementations, the elastic modulus of the fibers used in the mesophase asphalt-based carbon fiber layer is ≥400 GPa.
[0013] In the above scheme, if the elastic modulus of the fiber used in the mesophase asphalt-based carbon fiber layer is too small, the mesophase asphalt-based carbon fiber layer has a weak ability to resist deformation, and defects such as deformation or stress cracks are likely to occur during use, thereby reducing the service life of the mesophase asphalt-based carbon fiber layer.
[0014] In some feasible implementations, the carbon fibers in the acrylonitrile-based carbon fiber layer or the asphalt-based carbon fiber layer are arranged in at least one of a unidirectional structure and a woven fabric structure.
[0015] In the above scheme, the unidirectional structure means that all carbon fibers are arranged in the same direction. This arrangement allows the first reinforcing fiber layer and the second reinforcing fiber layer to have extremely high strength and rigidity in the fiber arrangement direction. The woven fabric structure means that multiple carbon fiber yarns are interwoven in a specific weaving method (such as plain, twill, satin, etc.). This arrangement allows the first reinforcing fiber layer and the second reinforcing fiber layer to have certain strength and rigidity in multiple directions.
[0016] In some feasible embodiments, the first reinforcing fiber layer is the same as the second reinforcing fiber layer.
[0017] In the above scheme, the first reinforcing fiber layer and the second reinforcing fiber layer are the same, that is, the materials of the surface layer and the back layer are the same, so as to ensure the flatness. At this time, the surface layer of the composite material has better performance consistency, so that during the heat conduction process, the thermal stress distribution of the composite material is more uniform, avoiding the composite material from being damaged due to excessive local stress, thereby increasing the service life of the composite; at the same time, the use of the same material can simplify the production process of the surface material, improve production efficiency and reduce production costs.
[0018] In some feasible implementations, the thickness of the first reinforcing fiber layer and the second reinforcing fiber layer is 20 μm to 200 μm.
[0019] In the above scheme, the first reinforcing fiber layer and the second reinforcing fiber layer are arranged on both sides of the intermediate phase asphalt-based carbon fiber layer to enhance the stiffness of the composite material. If the thickness of the first reinforcing fiber layer and the second reinforcing fiber layer is too large, the mass will increase, which will affect the total mass of the composite material, resulting in the composite material failing to meet the lightweight requirements; if the thickness of the first reinforcing fiber layer and the second reinforcing fiber layer is too thin, the stiffness will be reduced, and defects such as deformation or cracks are likely to occur during use, affecting the service life of the first reinforcing fiber layer and the second reinforcing fiber layer.
[0020] In some feasible embodiments, the elastic modulus of fibers used in the first reinforcing fiber layer and the second reinforcing fiber layer is ≥200 GPa.
[0021] In the above scheme, if the elastic modulus of the fibers used in the first reinforcing fiber layer and the second reinforcing fiber layer is too small, the ability of the first reinforcing fiber layer and the second reinforcing fiber layer to resist deformation is weak, and defects such as deformation or stress cracks are likely to occur during use, thereby reducing the service life of the first reinforcing fiber layer and the second reinforcing fiber layer.
[0022] In some feasible implementations, the composite material has a bright surface roughness Ra≤0.2 μm, and a matte surface roughness Ra≤1.0 μm.
[0023] In the above scheme, the surface roughness represents the flatness of the surfaces of the first reinforcing fiber layer and the second reinforcing fiber layer. If the surface roughness of the composite material is too large, the acrylonitrile-based carbon fiber layer and the asphalt-based carbon fiber layer cannot fit tightly with the contact surface of the internal components of the electronic device, and the air gap increases, resulting in a reduction in the effective contact area between the composite material and the internal components, thereby increasing the contact thermal resistance between the composite material and the internal components and reducing the thermal conduction efficiency of the composite material.
[0024] In some feasible implementations, the total thickness of the composite material is 60 μm to 600 μm.
[0025] In the above scheme, if the total thickness of the composite material is too large, the mass of the composite material will increase, resulting in the composite material failing to meet the lightweight requirements; if the total thickness of the composite material is too thin, the stiffness of the composite material will decrease, and the composite material will easily deform or crack during use, affecting the service life of the composite layer.
[0026] In some feasible embodiments, the average density of the composite material is ≤1.7 g / cm 3 .
[0027] In the above scheme, if the average density of the composite material is too large, it will affect the total mass of the prepared composite material, resulting in the composite material failing to meet the lightweight requirements.
[0028] In a second aspect, the present application provides a support plate, wherein the material of the support plate is the composite material described in any one of the first aspects.
[0029] In some feasible implementations, the support plate has a thickness of 60 μm to 600 μm.
[0030] In the above scheme, the support plate is used to support the display component in the electronic device. If the thickness of the support plate is too thick, the space occupied will increase and the mass of the support plate will increase, resulting in the support plate failing to meet the lightweight requirements; if the thickness of the support plate is too thin, the rigidity of the support plate will decrease, and defects such as deformation or cracks will easily occur during use, affecting the service life of the support plate.
[0031] In a third aspect, the present application provides an electronic device, including:
[0032] A support plate and a heat source device arranged inside the support plate;
[0033] Wherein, the support plate is the support plate according to any one of the second aspects, and at least one surface of the heat source device is in contact with the first reinforcing fiber layer and the second reinforcing fiber layer of the support plate.
[0034] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:
[0035] The composite material provided in the present application includes an intermediate phase asphalt-based carbon fiber layer and a first reinforcing fiber layer and a second reinforcing fiber layer arranged on both sides of the intermediate phase asphalt-based carbon fiber layer, wherein the intermediate phase asphalt-based carbon fiber layer has both high stiffness and good thermal conductivity, and the first reinforcing fiber layer and the second reinforcing fiber layer have the characteristics of high stiffness. After the first reinforcing fiber layer and the second reinforcing fiber layer are connected on both sides of the intermediate phase asphalt-based carbon fiber layer to prepare the composite material of the present application, the thickness and weight of the composite material can be reduced to meet the requirements of lightness and thinness, and the composite material also has good thermal conductivity and high stiffness. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 A structural schematic diagram of a carbon fiber arrangement of the composite material provided in this application;
[0037] Figure 2 A schematic structural diagram of another carbon fiber arrangement of the composite material provided in this application;
[0038] Figure 3 A schematic diagram of the structure of a composite material provided in this application;
[0039] Figure 4a , 4b A schematic diagram of the structure of a composite material provided in this application;
[0040] Figure 5 A schematic diagram of the structure of a composite material provided in this application;
[0041] Figure 6 A schematic diagram of the structure of a composite material provided in this application;
[0042] Figure 7 A schematic structural diagram of a composite material provided in this application.
[0043] Figure ID:
[0044] 1-mesophase pitch-based carbon fiber layer; 2-first reinforcing fiber layer; 3-second reinforcing fiber layer. DETAILED DESCRIPTION
[0045] In the description of the embodiments of the present application, it should be understood that the terms "length", "thickness", "up", "down", "front", "back", "left", "right", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more features. In the description of the embodiments of the present application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0046] In the description of the implementation methods of the present application, it should be noted that, unless otherwise clearly specified and limited, the term "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the implementation methods of the present application can be understood according to specific circumstances.
[0047] Some embodiments of the present application are further described in detail below in conjunction with the drawings of this specification.
[0048] With the continuous development of electronic devices such as mobile phones, users' demand for large-screen mobile phones has increased, but large-screen mobile phones are inconvenient to carry. Therefore, foldable screen mobile phones with extendable and deformable screens have become the main research direction. The foldable screen mobile phone connects the screen components of two adjacent areas through a hinge assembly. Specifically: the hinge assembly includes a hinge structure and a support plate. The screen assembly is covered on the support plate. The support plate and the hinge structure are rotatably connected, so that the adjacent screen assemblies can achieve smooth and safe folding and unfolding of the foldable screen mobile phone through the cooperation of the support plate and the hinge structure. During the folding and unfolding process of the foldable screen mobile phone, the support plate can effectively transfer the heat of the electronic components to the housing or other heat dissipation paths, and disperse the stress generated by the mobile phone during the folding process, reducing the problem of damage to the screen assembly due to uneven force during the folding and unfolding process.
[0049] However, the use of 5G electronic devices currently requires more signal and network data transmission, which causes the heat generated by electronic components, batteries, screen components and other structures in foldable screen mobile phones to increase sharply. At the same time, in order to meet users' higher performance requirements and thinner design requirements for foldable screen mobile phones, the performance requirements of the support plate put forward better design and manufacturing requirements. Therefore, finding a new material to prepare a thinner, stronger and more thermally conductive support plate is an issue that electronic equipment manufacturers need to consider.
[0050] In the prior art, metal support plates or polyacrylonitrile-based carbon fiber support plates are usually used to support the display part of electronic devices, but the above-mentioned support plates have certain problems when used. Specifically: the metal support plate has a large mass, which will increase the total mass of the folding screen mobile phone and cannot meet the demand for thin and light electronic devices; the polyacrylonitrile-based carbon fiber support plate has a low rigidity and is prone to defects such as deformation or cracks during use, which affects the service life. At the same time, the thermal conductivity of the polyacrylonitrile-based carbon fiber support plate is poor, and the heat generated by electronic components, batteries, screen components and other structures cannot be quickly and effectively transferred to the outer shell or other heat conduction paths, which easily causes the internal components to be in a high temperature state continuously, affecting the service life of electronic components, batteries, screen components and other structures.
[0051] In view of this, the present application provides a composite material, which includes at least one first reinforcing fiber layer 2, at least one second reinforcing fiber layer 3 and an intermediate phase asphalt-based carbon fiber layer 1 arranged therebetween; wherein the first reinforcing fiber layer 2 is an acrylonitrile-based carbon fiber layer or an asphalt-based carbon fiber layer, and the second reinforcing fiber layer 3 is an acrylonitrile-based carbon fiber layer or an asphalt-based carbon fiber layer.
[0052] In the above scheme, the composite material provided by the present application includes an intermediate phase asphalt-based carbon fiber layer 1 and a first reinforcing fiber layer 2 and a second reinforcing fiber layer 3 arranged on both sides of the intermediate phase asphalt-based carbon fiber layer 1, wherein the intermediate phase asphalt-based carbon fiber layer 1 has both high stiffness and good thermal conductivity, and the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 have the characteristics of high stiffness. After the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 are connected on both sides of the intermediate phase asphalt-based carbon fiber layer 1 to prepare the composite material of the present application, the thickness and weight of the composite material can be reduced to meet the requirements of lightness and thinness, and the composite material also has good thermal conductivity and high stiffness.
[0053] In some feasible embodiments, the mesophase asphalt-based carbon fiber layer 1 for providing heat conduction function is arranged inside the composite material, and heat can be transferred to the shell or other heat dissipation paths. It can be understood that the mesophase asphalt-based carbon fiber has a higher tensile modulus and strength than conventional asphalt-based carbon fiber materials, which can meet the high strength requirements of the composite material; at the same time, due to the graphite structure of the mesophase asphalt-based carbon fiber, its thermal conductivity is excellent, and the prepared mesophase asphalt-based carbon fiber layer 1 has better thermal conductivity.
[0054] In some feasible implementations, the carbon fiber arrangement in the mesophase asphalt-based carbon fiber layer 1 used in the present application is at least one of a unidirectional structure and a woven cloth structure, which can be selected according to actual needs and is not limited here.
[0055] As an optional technical solution of the present application, the carbon fiber arrangement in the intermediate phase asphalt-based carbon fiber layer 1 is a unidirectional structure, that is, all carbon fibers are arranged in the same direction. This arrangement can make the intermediate phase asphalt-based carbon fiber layer 1 have extremely high strength and rigidity in the fiber arrangement direction.
[0056] As an optional technical solution of the present application, the carbon fiber arrangement in the intermediate phase asphalt-based carbon fiber layer 1 is a woven cloth structure, that is, multiple carbon fiber yarns are interwoven according to a specific weaving method (such as plain weave, twill, satin, etc.). This arrangement method enables the intermediate phase asphalt-based carbon fiber layer 1 to have certain strength and rigidity in multiple directions.
[0057] In some feasible embodiments, the thickness of the mesophase asphalt-based carbon fiber layer 1 is 20 μm to 200 μm. Optionally, the thickness of the mesophase asphalt-based carbon fiber layer 1 can be 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm, 150 μm and 200 μm, etc., or other values within the range, which can be selected according to actual needs and are not limited here. It can be understood that the mesophase asphalt-based carbon fiber layer 1 is used in the heat conduction process. If the thickness of the mesophase asphalt-based carbon fiber layer 1 is too large, the mass increases, which will affect the total mass of the composite material, resulting in the composite material failing to meet the lightweight requirements; if the thickness of the mesophase asphalt-based carbon fiber layer 1 is too thin, the stiffness of the mesophase asphalt-based carbon fiber layer 1 is reduced, and defects such as deformation or cracks are prone to occur during use, affecting the service life of the mesophase asphalt-based carbon fiber layer 1.
[0058] It should be noted that when the thickness of the intermediate phase asphalt-based carbon fiber layer 1 of the present application is within the above range, the above thickness can be achieved by a single layer of intermediate phase asphalt-based carbon fiber layer 1, or the above thickness can be achieved by the total thickness of two or more intermediate phase asphalt-based carbon fiber layers 1 after pressing together. The combination of intermediate phase asphalt-based carbon fiber layers 1 of the above thickness can be selected according to actual needs, and is not limited here.
[0059] In some feasible embodiments, the thermal conductivity of the intermediate phase asphalt-based carbon fiber layer 1 is ≥ 400W / m·K. Optionally, the thermal conductivity of the intermediate phase asphalt-based carbon fiber layer 1 can be 400W / m·K, 500W / m·K, 600W / m·K, 700W / m·K, 800W / m·K, 900W / m·K, 1000W / m·K, 1100W / m·K and 1200W / m·K, etc., or other values within the range, which can be selected according to actual needs and are not limited here. It can be understood that the thermal conductivity of the intermediate phase asphalt-based carbon fiber layer 1 is an important parameter for measuring the thermal conductivity of the intermediate phase asphalt-based carbon fiber layer 1. If the thermal conductivity of the intermediate phase asphalt-based carbon fiber layer 1 is too small, the thermal conduction efficiency of the intermediate phase asphalt-based carbon fiber layer 1 is not high, and the heat generated by the internal components of the electronic device cannot be quickly and effectively transferred to the outer casing or other heat conduction paths, which easily causes the internal components to be continuously in a high temperature state, affecting the service life of the internal components.
[0060] In some feasible embodiments, the elastic modulus of the fibers used in the mesophase asphalt-based carbon fiber layer is ≥400GPa. Optionally, the elastic modulus of the fibers used in the mesophase asphalt-based carbon fiber layer is 400GPa, 500GPa, 600GPa, 700GPa, 800GPa, 900GPa, and 1000GPa, etc., or other values within the range, which can be selected according to actual needs and are not limited here. It is understandable that if the elastic modulus of the fibers used in the mesophase asphalt-based carbon fiber layer is too small, the mesophase asphalt-based carbon fiber layer 1 has a weak ability to resist deformation, and defects such as deformation or stress cracks are prone to occur during use, reducing the service life of the mesophase asphalt-based carbon fiber layer 1.
[0061] In some feasible embodiments, the carbon fiber arrangement in the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 for further enhancing the stiffness of the composite material is at least one of a unidirectional structure and a woven cloth structure, which can be selected according to actual needs and is not limited here.
[0062] As an optional technical solution of the present application, the carbon fiber arrangement in the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 is a unidirectional structure, please refer to Figure 1 All carbon fibers are arranged in the same direction. This arrangement allows the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 to have extremely high strength and rigidity in the fiber arrangement direction.
[0063] As an optional technical solution of the present application, the carbon fiber arrangement in the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 is a woven fabric structure, please refer to Figure 2A plurality of carbon fiber yarns are interwoven according to a specific weaving method (such as plain weave, twill weave, satin weave, etc.). This arrangement enables the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 to have certain strength and rigidity in multiple directions.
[0064] In some feasible embodiments, the composite material includes at least one first reinforcing fiber layer 2 and second reinforcing fiber layer 3, and the materials and thicknesses of the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 may be the same or different. That is, when the surface of the mesophase asphalt-based carbon fiber layer 1 abutting against the screen component is defined as the top surface and the surface away from the screen component is defined as the bottom surface in the present application, the types of layers arranged on the top surface and the bottom surface may be the same or different.
[0065] As an optional technical solution for this application, please refer to Figure 3 The composite material of the present application includes a first reinforcing fiber layer 2, an intermediate phase asphalt-based carbon fiber layer 1 and a second reinforcing fiber layer 3 which are stacked in sequence from the top surface to the bottom surface, and the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 on both sides of the intermediate phase asphalt-based carbon fiber layer 1 are made of the same material and have the same thickness.
[0066] As an optional technical solution for this application, please refer to Figure 4a and Figure 4b The composite material of the present application includes a first reinforcing fiber layer 2, an intermediate phase asphalt-based carbon fiber layer 1 and a second reinforcing fiber layer 3 which are stacked in sequence from the top surface to the bottom surface, and the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 on both sides of the intermediate phase asphalt-based carbon fiber layer 1 are made of the same material but have unequal thicknesses.
[0067] As an optional technical solution of the present application, the composite material of the present application includes a first reinforcing fiber layer 2, an intermediate phase asphalt-based carbon fiber layer 1 and a second reinforcing fiber layer 3 which are stacked in sequence from the top surface to the bottom surface, and the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 on both sides of the intermediate phase asphalt-based carbon fiber layer 1 are made of different materials and have equal thicknesses.
[0068] As an optional technical solution for this application, please refer to Figure 5 The composite material of the present application includes two first reinforcing fiber layers 2, a mesophase asphalt-based carbon fiber layer 1 and a second reinforcing fiber layer 3 which are stacked in sequence from the top surface to the bottom surface.
[0069] As an optional technical solution for this application, please refer to Figure 6 The composite material of the present application includes a first reinforcing fiber layer 2, a mesophase asphalt-based carbon fiber layer 1 and two second reinforcing fiber layers 3 which are stacked in sequence from the top surface to the bottom surface.
[0070] As an optional technical solution for this application, please refer to Figure 7 The composite material of the present application includes two first reinforcing fiber layers 2, one mesophase asphalt-based carbon fiber layer 1 and two second reinforcing fiber layers 3 which are stacked in sequence from the top surface to the bottom surface.
[0071] In addition to the above description, the composite material can also be other different combinations of the first reinforcing fiber layer 2, the intermediate phase asphalt-based carbon fiber layer 1 and the second reinforcing fiber layer 3, which can be selected according to the actual stiffness improvement needs and are not limited here.
[0072] In some feasible embodiments, the first reinforcing fiber layer 2 is the same as the second reinforcing fiber layer 3 to ensure flatness. It can be understood that the materials of the layers on both sides of the intermediate phase asphalt-based carbon fiber layer 1 are the same, that is, the materials of the surface layer and the back layer are the same. At this time, the surface layer of the composite material has better performance consistency, so that during the heat conduction process, the thermal stress distribution of the composite material is more uniform, avoiding damage to the composite material due to excessive local stress, thereby increasing the service life of the composite; at the same time, the use of the same material can simplify the production process of the surface material, improve production efficiency, and reduce production costs.
[0073] In some feasible embodiments, the thickness of the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 is 20 μm to 200 μm. Optionally, the thickness of the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 can be 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm, 150 μm and 200 μm, etc., or other values within the range, which can be selected according to actual needs and are not limited here. It can be understood that the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 are arranged on both sides of the intermediate phase asphalt-based carbon fiber layer 1 to enhance the stiffness of the composite material. If the thickness of the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 is too large, the mass increases, which will affect the total mass of the composite material, resulting in the composite material failing to meet the lightweight requirements; if the thickness of the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 is too thin, the stiffness is reduced, and defects such as deformation or cracks are prone to occur during use, affecting the service life of the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3.
[0074] It should be noted that, when the thickness of the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 of the present application is within the above range, the above thickness can be achieved by a single layer of the first reinforcing fiber layer 2 and / or a single layer of the second reinforcing fiber layer 3, or the total thickness of more than two layers of the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 after pressing together can reach the above thickness. The combination of the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 of the above thickness can be selected according to actual needs, and is not limited here.
[0075] In some feasible embodiments, the elastic modulus of the fibers used in the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 is ≥ 200 GPa. Optionally, the elastic modulus of the fibers used in the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 can be 200 GPa, 400 GPa, 500 GPa, 600 GPa, 700 GPa, 800 GPa, 900 GPa and 1000 GPa, etc., or other values within the range, which can be selected according to actual needs and are not limited here. It is understandable that if the elastic modulus of the fibers used in the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 is too small, the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 have weak ability to resist deformation, and defects such as deformation or stress cracks are likely to occur during use, reducing the service life of the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3.
[0076] In some feasible embodiments, the bright surface roughness Ra of the composite material is ≤0.2 μm, and the matte surface roughness Ra is ≤1.0 μm. Optionally, the bright surface roughness Ra of the composite material can be specifically 0.2 μm, 0.18 μm, 0.16 μm, 0.14 μm, 0.13 μm and 0.10 μm, etc., and the matte surface roughness Ra can be specifically 1.0 μm, 0.9 μm, 0.8 μm, 0.7 μm, 0.6 μm and 0.5 μm, etc., or other values within the range, which can be selected according to actual needs and are not limited here. It can be understood that the surface roughness characterizes the flatness of the surface of the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3. If the bright surface roughness and the matte surface roughness of the composite material are too large, the first reinforcing fiber layer 2 and the second reinforcing fiber layer 3 cannot be closely attached to the contact surface of the internal components of the electronic device, and the air gap increases, resulting in a reduction in the effective contact area between the composite material and the internal components, increasing the contact thermal resistance between the composite material and the internal components, and reducing the thermal conduction efficiency of the composite material.
[0077] In some feasible embodiments, the total thickness of the composite material is 60 μm to 600 μm. Optionally, the total thickness of the composite material can be 60 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm and 600 μm, etc., or other values within the range, which can be selected according to actual needs and are not limited here. It is understandable that if the total thickness of the composite material is too large, the mass of the composite material will increase, resulting in the composite material failing to meet the lightweight requirements; if the total thickness of the composite material is too thin, that is, the thickness of the first reinforcing fiber layer 2, the intermediate phase asphalt-based carbon fiber layer 1 or the second reinforcing fiber layer 3 constituting the composite material is too large, the stiffness of the composite material will be reduced, and the composite material will be prone to defects such as deformation or cracks during use, affecting the service life of the composite layer.
[0078] In the second aspect, the present application provides a support plate, which is made of the composite material of any one of the first aspects by hot pressing, molding, vacuum bag pressing, and vacuum can pressing. The pressing method of the composite material can be selected according to actual needs and is not limited here. The thickness of the support plate obtained after pressing the composite material is not much different from that of the composite material.
[0079] It should be noted that after the composite material has been pressed, it is also necessary to prepare a support plate that is thinner, stronger and has better thermal conductivity through punching, machining, laser cutting and other methods.
[0080] As an optional technical solution of the present application, hot pressing or compression molding refers to a process in which a preformed composite material is placed in a heated mold and cured under high temperature and high pressure.
[0081] As an optional technical solution of the present application, the vacuum bag pressing method refers to laying the first reinforcing fiber layer 2, the second reinforcing fiber layer 3, and the intermediate phase asphalt-based carbon fiber layer 1 on a mold, and then sealing the mold and the layered structure with a vacuum bag, vacuuming to remove the air and using atmospheric pressure to press the resin into the carbon fibers of the layered structure, and then completing the resin curing process under heating conditions.
[0082] As an optional technical solution of the present application, vacuum tank pressing refers to placing a mold of the prepreg containing the layered first reinforcing fiber layer 2, the second reinforcing fiber layer 3, and the intermediate phase asphalt-based carbon fiber layer 1 in a large autoclave container capable of regulating temperature and pressure, and ensuring that the prepreg is completely cured under uniform pressure and temperature through vacuuming, pressurizing and precise temperature control to obtain a laminated support plate.
[0083] In some feasible embodiments, the thickness of the support plate is 60 μm to 600 μm. Optionally, the thickness of the support plate can be 60 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm and 600 μm, etc., or other values within the range. It can be selected according to actual needs and is not limited here. It can be understood that the support plate is obtained by laminating the composite material, so the total thickness of the support plate is less than the total thickness of the composite material. The laminating support plate is used to support the display component in the electronic device. If the thickness of the support plate is too thick, the space occupied increases, and the weight of the support plate is increased, resulting in the support plate failing to meet the lightweight requirements; if the thickness of the support plate is too thin, that is, the thickness of the composite material used to prepare the support plate is too thin, the rigidity of the support plate will be reduced, and defects such as deformation or cracks are prone to occur during use, affecting the service life of the support plate.
[0084] The technical solution of the present application is described below in conjunction with specific embodiments:
[0085] Embodiment 1:
[0086] (1) In a hot press mold, an acrylonitrile-based carbon fiber woven fabric prepreg with a thickness of 25 μm, a mesophase pitch-based carbon fiber woven fabric prepreg with a thickness of 100 μm, and an acrylonitrile-based carbon fiber woven fabric prepreg with a thickness of 25 μm are stacked in sequence.
[0087] (2) The mold is placed in a vacuum bag and put into an autoclave and heated to 90°C. After preheating for a period of time, the temperature is raised to 130°C and the pressure is increased for pressing for 120 minutes. The mold is then cooled to room temperature and taken out. After being punched by a tool, a support plate of a specific shape is obtained.
[0088] Embodiment 2:
[0089] (1) In a hot pressing mold, an acrylonitrile-based carbon fiber woven fabric prepreg with a thickness of 30 μm, an intermediate phase pitch-based carbon fiber unidirectional tape prepreg with a thickness of 90 μm, and an acrylonitrile-based carbon fiber woven fabric prepreg with a thickness of 30 μm are stacked in sequence.
[0090] (2) The mold is placed in a vacuum bag and put into an autoclave and heated to 90°C. After preheating for a period of time, the temperature is raised to 130°C and the pressure is increased for pressing for 120 minutes. The mold is then cooled to room temperature and taken out. After being punched by a tool, a support plate of a specific shape is obtained.
[0091] Comparative Example 1
[0092] A titanium alloy support plate with a thickness of 150μm is used.
[0093] Comparative Example 2
[0094] A polyacrylonitrile-based carbon fiber support plate with a thickness of 150 μm was used.
[0095] test:
[0096] Thickness test of support plate: using micrometer test;
[0097] Stiffness test of support plate: three-bar bending test is adopted;
[0098] Average density test of support plate: using density meter;
[0099] Thermal conductivity test: using laser thermal conductivity meter.
[0100] Test results:
[0101] Table 1
[0102]
[0103]
[0104] Test result analysis:
[0105] It can be seen from the test results of Examples 1 to 2 and Comparative Examples 1 to 2 that after the first reinforcing fiber layer and the second reinforcing fiber layer are connected on both sides of the intermediate phase asphalt-based carbon fiber layer to prepare the composite material of the present application, the obtained composite material has lightness, good thermal conductivity and high stiffness.
[0106] It should be noted that the composite material provided in the present application can be used not only on the support plate of foldable screen mobile phones, but also on other electronic devices that require thermal conductivity and high rigidity. Other electronic devices include but are not limited to tablet computers, laptops, car computers, display devices (such as TVs), wearable devices, personal digital assistants (PDA) or newly developed electronic devices, etc., which can be selected according to actual needs and are not limited here.
[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the utility model, rather than to limit it. Although the utility model has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the utility model.
Claims
1. A support plate, characterized in that: The support plate includes at least one first reinforcing fiber layer, at least one second reinforcing fiber layer and an intermediate phase asphalt-based carbon fiber layer arranged therebetween; wherein the first reinforcing fiber layer is an acrylonitrile-based carbon fiber layer or an asphalt-based carbon fiber layer, and the second reinforcing fiber layer is an acrylonitrile-based carbon fiber layer or an asphalt-based carbon fiber layer.
2. The support plate according to claim 1, characterized in that: The carbon fibers in the mesophase pitch-based carbon fiber layer are arranged in at least one of a unidirectional structure and a woven fabric structure.
3. The support plate according to claim 1, characterized in that: The thickness of the mesophase pitch-based carbon fiber layer is 20 μm to 200 μm.
4. The support plate according to claim 1, characterized in that: The thermal conductivity of the mesophase asphalt-based carbon fiber layer is ≥400 W / m·K.
5. The support plate according to claim 1, characterized in that: The elastic modulus of the fibers used in the mesophase asphalt-based carbon fiber layer is ≥400 GPa.
6. The support plate according to claim 1, characterized in that: The carbon fibers in the acrylonitrile-based carbon fiber layer or the asphalt-based carbon fiber layer are arranged in at least one of a unidirectional structure and a woven fabric structure.
7. The support plate according to claim 1, characterized in that: The first reinforcing fiber layer is identical to the second reinforcing fiber layer.
8. The support plate according to claim 7, characterized in that: The thickness of the first reinforcing fiber layer and the second reinforcing fiber layer is 20 μm to 200 μm.
9. The support plate according to claim 7, characterized in that: The elastic modulus of the fibers used in the first reinforcing fiber layer and the second reinforcing fiber layer is ≥200 GPa.
10. The support plate according to any one of claims 1 to 9, characterized in that: The support plate has a bright surface roughness Ra≤0.2 μm and a matte surface roughness Ra≤1.0 μm.
11. The support plate according to any one of claims 1 to 9, characterized in that: The total thickness of the support plate is 60 μm to 600 μm.
12. The support plate according to any one of claims 1 to 9, characterized in that: The average density of the support plate is ≤1.7g / cm 3 .
13. An electronic device, characterized in that: include: A support plate and a heat source device arranged inside the support plate; Wherein, the support plate is the support plate according to any one of claims 1 to 12, and at least one surface of the heat source device is in contact with the first reinforcing fiber layer or the second reinforcing fiber layer of the support plate.
Citation Information
Cited By
Structural component of electronic equipment, preparation method of structural component and electronic equipment
CN120716251A